Critical Upper Limb Ischemia due to Subclavian Artery Compression Caused by Initially Undiagnosed Cervical Rib - A Case Report - Mahmud, Sultan; Khan, Omar Sadeque; Mamun, Abdullah Al; Hossain, Fidah; Aftabuddin, Md; Adhikary, Asit Baran; Saklayen, SMG (University Heart Journal, 2016)
True subclavian artery aneurysms are relatively rare events. Thoracic outlet compression is responsible for 75% of those aneurysms. They are formed as a result of compression of subclavian artery, for example a cervical rib. A case of subclavian artery aneurysm secondary to cervical rib in a 35 year old young adult, who presented with a critical ischemia in his dominant right upper limb. Plain x-ray of cervical spine revealed bilateral cervical ribs and duplex study of the both upper limb arteries concluded aneurysmal dilatation of mid-distal subclavian artery of both sides with mural thrombus on the right side, marked distal ischemia in the right upper limb due to occlusive thrombus in the distal arterial tree, normal distal arterial flow in the left upper limb. Although it is a rare lesion, cervical rib leading to thoracic outlet compression should always be included in the differential diagnosis of a critically ischemic limb in young age group. Surgical management should be considered in a patient with subclavian artery aneurysm due to cervical rib to prevent additional embolic events. University Heart Journal Vol. 11, No. 1, January 2015; 48-51